Sarcoidosis and lymphoma in the same patient. Issue 695 (September 1983) - Brennan, N. J.; Fennelly, J. J.; Towers, R. P.; FitzGerald, M. X.
Abstract : A case of lymphocytic lymphoma in a patient with coincidental sarcoidosis is described, and the possible relationship of the two conditions is discussed. A revised set of diagnostic criteria is proposed to overcome previous difficulties encountered in validating such dual pathology.